Map kinase MGV1: a potential shared control point of butenolide and deoxynivalenol biosynthesis. - Rampitsch, Christof; Leung, Winnie; Blackwell, Barbara; Subramaniam, Rajagopal (Plant Breeding and Seed Science, 2011)
The mitogen-activated protein kinase (MAPK) MGV1 has been knocked out in Fusarium graminearum to produce the mutant Fg∆MGV1. The mutant displays complementary phenotypes concerning deoxynivalenol (DON) and butenolide (BT) biosynthesis in vitro. In the rich medium 15-ADON accumulates are at low levels as detected by HPLC, whereas the accumulation of BT is substantial in Fg∆MGV1. This is supported by the high expression of butenolide cluster genes in the mutant compared to the wild-type strain. Under nutrient-limiting conditions, where DON biosynthesis is normally favoured, the expression of genes of the trichothecene cluster does not differ between the two strains. However, the accumulation of 15-ADON is vastly different in Fg∆MGV1. There is a reduction of 15-ADON accumulation with a concomitant accumula- tion of a novel compound. Although gene clusters comprising the synthesis of DON and BT have been identi- fied, their regulation at the molecular level has not been fully elucidated. Since the expression levels of two regulatory genes from the trichothecene gene cluster and three regulatory genes from the butenolide gene cluster remained unchanged between WT and Fg∆MGV1, we suggest that differential accumulation of both BT and DON biosynthesis is at least partially under post-transcriptional and/or post-translational control.